Comparison of Three Lateral Flow Immunoassay Formats for the Detection of Antibodies against the SARS-CoV-2 Antigen - Dmitriy V. Sotnikov; Nadezhda A. Byzova; Anatoly V. Zherdev; Youchun Xu; Boris B. Dzantiev (Biosensors, 2023)
Reliable detection of specific antibodies against pathogens by lateral flow immunoassay (LFIA) greatly depends on the composition of the detectable complex and the order of its assembly. We compared three LFIA formats for revealing anti-SARS-CoV-2 antibodies in sera with the following detected complexes in the analytical zone of the strip: antigen–antibodies–labeled immunoglobulin-binding protein (Scheme A); antigen–antibodies–labeled antigen (Scheme B); and immunoglobulin-binding protein–antibodies–labeled antigen (Scheme C). The lowest detection limit was observed for Scheme C, and was equal to 10 ng/mL of specific humanized monoclonal antibodies. When working with pooled positive sera, Scheme C had a detection limit 15 times lower than Scheme B and 255 times lower than Scheme A. Due to the high sensitivity of Scheme C, its application for the panel of human sera (n = 22) demonstrated 100% diagnostic specificity and sensitivity. These consistent results be useful for designing the format of LFIA serodiagnosis for other diseases.